ANALISIS PENGUASAAN RADIKAL AKSARA MANDARIN PADA MAHASISWA ANGKATAN 2015 PENDIDIKAN BAHASA MANDARIN UNIVERSITAS TANJUNGPURA - Utari, Sri; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractRadial is a unit of structure between the strokes and the whole word in a compound Chinese structure. Chinese radical is divided into two categories, one is meaning radical; the other is phonetic radical. The function of the meaning radical is to indicate the meaning of the word, and the function of the phonetic radical is to express the pronunciation of the word. However, with the development of Chinese characters, some of the meaning radical effects have changed or disappeared, which have caused difficulties for students to learn radical. In order to understand the mastery and difficulty ofÂ  Chinese characters to the students on year 2015 Chinese language education study of Tanjungpura University, author uses the test method to test students to understand their mastery and analyze the difficulties of Chinese radical. The test results show that students have a better grasp of the radical deviation of Chinese phonetic than the meaning of Chinese characters. Then, according to the analysis and test results, the author finds that the difficulty of students in mastering Chinese characters is the representative meaning of Chinese characters and the variations of meaning and pronunciation of pronunciation and present.Â Key words: Chinese radical,Meaning radical,Phonetic radical